SAGITTAL BALANCE IN ADOLESCENT IDIOPATHIC SCOLIOSIS - PINTO,EDUARDO MOREIRA (2019)
ABSTRACT Objective The objective of this study is to achieve a better understanding of the parameters that influence sagittal balance in a population with adolescent idiopathic scoliosis (AIS). Methods A retrospective study of 80 patients with adolescent idiopathic scoliosis (AIS) was conducted. The parameters evaluated were: age, sex, pelvic incidence (PI), sacral slop (SS), pelvic tilt (PT), sagittal balance (SB), coronal balance (CB), lumbar lordosis (LL), thoracic kyphosis (TK) divided into upper (between T1 and T5) and lower (between T5 and T12), cervical spine alignment (CSA), and Cobb’s coronal angle (CCA) of primary scoliotic curvature. Results Regarding the sagittal balance, this study demonstrated a significant statistical positive correlation with cervical shape (p<0.01) and upper thoracic kyphosis (from T1 to T5) (p<0.05), but not with the other variables. LL had a strong influence on lower thoracic curvature (from T5 to T12) and was strongly influenced by the PI and SS. Conclusions Sagittal balance is a parameter that is influenced by multiple factors. In fact, it is closely related to cervical shape and the upper thoracic curvature (from T1 to T5), which in turn, is closely linked to the severity of the scoliotic kyphosis. The Cobb angle of the lower thoracic spine (from T5 to T12) is more closely correlated with the angle of lumbar lordosis than with the upper thoracic kyphosis (from T1 to T5). Level of evidence IV; Case Series.